ANALISIS PERKEMBANGAN USAHA PENERIMA BANTUAN PRODUKTIF USAHA MIKRO (BPUM) PERSPEKTIFEKONOMI ISLAM (STUDI KASUS KECAMATAN PANYABUNGAN KABUPATEN MANDAILING NATAL) - Nurul Hidayah Nst; Imsar; Atika (EKSYA : Jurnal Ekonomi Syariah, 2022)
Business development of Micro Business Productive Assistance Recipients (BPUM), The research method used is a qualitative method. Data collection techniques using observation, interviews and documentation methods are conducting direct interviews with SME actors who receive Micro Business Productive Assistance (BPUM) in Panyabungan District. The results of this study can be concluded that the Productive Micro Business Assistance (BPUM) in Panyabungan District according to its provisions is used for additional business capital so that SME businesses can survive and thrive in the midst of the Covid-19 Pandemic, but in fact in Panyabungan District the SMEs who receive the funds have not fully used these funds for additional business capital due to various factors, the funds obtained were Rp. 2,400,000 channeled through Bank Rakyat Indonesia (BRI) to the beneficiary's account. This Micro Business Productive Assistance (BPUM), in Islamic economics is known as Hibah, which is a voluntary gift to improve oneself to Allah without expecting anything in return. Grants are a form of mutual assistance in the virtue of good fellow human beings and have positive values, and as a fund leader (BPUM) it is his responsibility for the welfare of his community.